Xenopus: Driving the Discovery of Novel Genes in Patient Disease and Their Underlying Pathological Mechanisms Relevant for Organogenesis - Hwang, Woong Y.; Marquez, Jonathan; Khokha, Mustafa K. (Frontiers in Physiology, 2019)
Frog model organisms have been appreciated for their utility in exploring physiological phenomena for nearly a century. Now, a vibrant community of biologists that utilize this model organism has poised Xenopus to serve as a high throughput vertebrate organism to model patient-driven genetic diseases. This has facilitated the investigation of effects of patient mutations on specific organs and signaling pathways. This approach promises a rapid investigation into novel mechanisms that disrupt normal organ morphology and function. Considering that many disease states are still interrogated in vitro to determine relevant biological processes for further study, the prospect of interrogating genetic disease in Xenopus in vivo is an attractive alternative. This model may more closely capture important aspects of the pathology under investigation such as cellular micro environments and local forces relevant to a specific organ’s development and homeostasis. This review aims to highlight recent methodological advances that allow investigation of genetic disease in organ-specific contexts in Xenopus as well as provide examples of how these methods have led to the identification of novel mechanisms and pathways important for understanding human disease.